2017
DOI: 10.1016/j.semcdb.2016.08.022
|View full text |Cite
|
Sign up to set email alerts
|

The Sox transcriptional factors: Functions during intestinal development in vertebrates

Abstract: The intestine has long been studied as a model for adult stem cells due to the life-long self-renewal of the intestinal epithelium through the proliferation of the adult intestinal stem cells. Recent evidence suggests that the formation of adult intestinal stem cells in mammals takes place during the thyroid hormone-dependent neonatal period, also known as postembryonic development, which resembles intestinal remodeling during frog metamorphosis. Studies on the metamorphosis in Xenopus laevis have revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 147 publications
0
8
0
Order By: Relevance
“…Moreover, the implanted human cells successfully recruited tunica external and media cells from the mouse body to form a mature vasculature structure, as evidenced by IF staining for human CD31 (endothelial layer, internal), anti‐mouse α‐SMA (smooth muscle cells, middle), and anti‐mouse vimentin (connective tissue, external; Figure h). Besides, the transcriptional levels of both Lgr5+/PRMT and Sox9/GATA4, which are important genes during intestinal and hepatic epithelium generation, were up‐regulated as Caco2 and Hep G2 grew. Similarly, early neurogenic markers, such as Fgf5 for primitive ectoderm and Sox1 for neuroectoderm, were expressed along the cultivation of SH‐SY5Y in THAG.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the implanted human cells successfully recruited tunica external and media cells from the mouse body to form a mature vasculature structure, as evidenced by IF staining for human CD31 (endothelial layer, internal), anti‐mouse α‐SMA (smooth muscle cells, middle), and anti‐mouse vimentin (connective tissue, external; Figure h). Besides, the transcriptional levels of both Lgr5+/PRMT and Sox9/GATA4, which are important genes during intestinal and hepatic epithelium generation, were up‐regulated as Caco2 and Hep G2 grew. Similarly, early neurogenic markers, such as Fgf5 for primitive ectoderm and Sox1 for neuroectoderm, were expressed along the cultivation of SH‐SY5Y in THAG.…”
Section: Resultsmentioning
confidence: 99%
“…SOX genes, members of the high mobility group superfamily, primarily encode transcription factors ( 28 , 29 ). SOX genes have been demonstrated to be associated with the differentiation and proliferation of cells ( 30 ), and have oncogene functions ( 31 , 32 ). It is reported that SOX10 and SOX1 are tumor-associated antigens of melanoma and small cell lung cancer cells, respectively ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…SOX genes play a crucial role in the regulation of sex determination, osseous development, hemocyte formation, nervous system development, and crystalline development. 19 SOX5, a member of the SOX gene family, is expressed in normal spermoblasts, neurocytes, oligodendrocytes, and chondrocytes. 20 , 21 , 22 Emerging evidence has proven that SOX5 is related to the occurrence and progression of tumors.…”
Section: Introductionmentioning
confidence: 99%